Reconstructing the Law of Nasab for Children Born with a Gestation Period of Less Than Six Months through a Critical Analysis of the Perlis State Fatwa Based on Maqāṣid Al-Syarī’ah - Bin Omar, Muhammad Nor Sulaimi; Mustaqilla, Safira (Prodi Hukum Keluarga Fakultas Syariah dan Hukum UIN Ar-Raniry, 2025)
The phenomenon of children being born with a gestational period of less than six months after the marriage contract (premarital conception) has created a crisis of legal dualism in Malaysia. The majority of Malaysian states, following the National Fatwa, reject the attribution of lineage (nasab) of such children to their mother’s husband and mandate the use of “bin Abdullah,” which generates social stigma and long-term psychological consequences. In contrast, the Fatwa Committee of the State of Perlis issued a reformist opinion that allows the attribution of lineage to the mother’s husband if certain conditions are met. This study aims to critically analyze the methodological construction of the Perlis Fatwa in comparison with the National Fatwa, as well as to evaluate the relevance of both fatwas from the perspective of Maqāṣid al-Sharī‘ah (the objectives of Islamic law) and the protection of children’s rights in the modern context. The research employs a juridical-normative method using a statute approach. Primary data sources include the texts of the National Fatwa and the Perlis State Fatwa, along with official explanatory documents from the Mufti of Perlis. The data are analyzed using content analysis techniques and uṣūlī comparison to examine the evidences and methods of legal reasoning (istinbāṭ al-ḥukm). The study finds that the Perlis Fatwa does not intend to legalize fornication (zinā), but rather applies the principles of Sitr (concealing faults), Hifz al-Nafs, and Hifz al-‘Ird, which are considered more dominant than the formalistic textual approach of Hifz al-Nasl upheld by the National Fatwa. The Perlis Fatwa is strongly grounded in the opinions of minority classical scholars and is highly relevant to the principle of justice for innocent children. This research offers a new synthesis between classical Islamic law and modern sociological realities, recommending legal harmonization that prioritizes the welfare of children without compromising the principles of sharī‘ah, while also filling the gap in the literature regarding the maqāṣid-based justification of the Perlis Fatwa.